PENINGKATAN HASIL BELAJAR PADA PEMBELAJARAN MATEMATIKA MELALUI MODEL PEMBELAJARAN INSTANT ASSESMENT DENGAN MEDIA CHOOSE NUMBER DI KELAS III SDN 08 KUMBAYAU - Yusra Gusvifta (JURNAL MANAJEMEN PENDIDIKAN, 2019)
Based on the learning outcomes of Class III students of SDN 08 Kumbayau in learning mathematics, it was found that many student learning outcomes in mathematics learning were incomplete. The purpose of this study was to describe and obtain information about improving student learning outcomes in Mathematics Learning through the Instant Learning Assessment Model with Media Choose Number in Class III SDN 08 Kumbayau. This research is Classroom Action Research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 25 students of Class III SDN 08 Kumbayau. Research data were collected using a test sheet. Data were analyzed using percentages. Based on the results of research and discussion that has been proposed, it can be concluded that the learning model of the Instant Assessment Learning Model with the media choose number can improve student learning outcomes in Mathematics Learning in Class III SDN 08 Kumbayau. Student learning outcomes in the first cycle were 72.90 increased to 83.87 with an increase of 10.97%.